Challenges to democratic participation : antipolitics, deliberative democracy, and pluralism - Campos, Andre Santos, 1980- (Lexington Books, 2014)
Challenges to Democratic Participation focuses on three major trends of contemporary theoretical challenges to participatory democracy: antipolitics, deliberative democracy, and pluralism. It is accessible and useful to a wide variety of audiences, from scholars and practitioners working in political science to activists and citizens interested in the theoretical setting of democratic practices. It also enhances current scholarship, serving as a guide to existing research and identifying useful future research.